Collaborative Efforts Between Disperindag Jatim and PT Feihuang in Increasing Halal Food and Beverages to China - Anggita Putri Syarafinna, (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2025)
Business matching is an activity where businesses and buyers meet with the same commodity background to create an exchange of information about market characteristics and consumer preferences of each party. Seeing this potential, the East Java Provincial Industry and Trade Office (Disperindag Jatim) organized offline business matching on November 14, 2024 to bring together halal-certified food and beverage sector MSME players from East Java with prospective buyers from China. This study aims to explain the collaborative efforts through business matching conducted by the East Java Disperindag in collaboration with PT Feihuang. The novelty of this research lies in exploring how regional government and private sector collaboration serves as a strategic model to facilitate halal product exports through business matching activities. The method used is descriptive qualitative with data collected in primary data collection through interviews with the Head of the East Java Disperindag Export Promotion Division and secondary data in the form of activity documents and literature studies, analyzed using the Miles and Huberman interactive model consisting of data collection, reduction and conclusion drawing. The results showed that this business matching activity successfully facilitated the exchange of strategic information related to market preferences between countries and became the first step in building mutually beneficial and long-term oriented trade cooperation.